INTRODUCCIÓN AL ESTUDIO DEL ESTATUS EPISTEMOLÓGICO DE LAS CIENCIAS ADMINISTRATIVAS EN MARIO BUNGE - López Mas, Julio (2008)
The administrative sciences have as object of study the organizations, that develop through decisions taken and, although they are helped in diverse sciences and technical’s, it maintains a specific character, showing hierarchical and temporary unit, instrumental value, amplitude, interdisciplinary nature and flexibility. The article analyzes critically the position of Bunge on the epistemological nature of the administrative sciences.